The impact of ecotourism development towards the quality of life as perceived by local communities at National Forest Park, Malaysia - Ahmad Firdaus Ahmad Radzi; Bageshree S Segar; Muhammad Syafiq Nawayee; Nur Afifah Abd Rashid (2021)
This research presents the study on the impact of ecotourism in social, economic, and environmental towards the quality of life as perceived by local communities in National Forest Park, Malaysia. Ecotourism can be defined as responsible travel to natural areas that preserve the environment, maintain the well-being of the local community, and involve interpretation and education. Education is meant to include staff and guests. Ecotourism is about uniting conservation, communities, and sustainable travel. In this study, the researcher used a quantitative methodology to accomplish this research. Cluster sampling has been used and responses from 290 are collected. To analyze all the data, descriptive analysis, reliability testing, and Pearson Correlation are used. The results support all the variables. This research contributes to understanding the quality of life of local communities on the impact of ecotourism activities. This research and data can be used as reference materials for future research in the tourism industry.